Ageing in emerging markets / Lady English. - English, Lady (Universiti Teknologi Mara Selangor, 2016)
In January 2015, I attended the Emerging Markets Symposium on Ageing, held in Oxford, UK. A group of 50 experts, from 20 countries and a range of relevant disciplines, collaborated to produce recommendations designed to be of practical value to policymakers faced with the challenges of population ageing. The topic is timely because the proportion of the population over age 65 is increasing in Emerging Market countries at an accelerated rate; changes that developed over 150 years in developed countries such as Britain or the USA will occur over a period of 25 years in the Emerging Markets (EMs). This article will highlight the main themes from the Symposium and encourage interested readers to move on to the full report (see below). Why are so many countries facing this demographic change? The rise in the proportion of elderly people reflects three positive trends following economic growth: - The fall in infant and child mortality - Reduced fertility rates - Rising longevity as a result of improved nutrition, public health and medical care